AFFECTIVE TEACHING AND TEACHER QUALITY: INSIGHTS FROM MALAYSIAN PRIMARY LANGUAGE ARTS CLASSROOMS - Flora Crispina Nathan; Dorothy Dewitt; Lim Jia Wei (MOJES: Malaysian Online Journal of Educational Sciences, 2025)
This qualitative case study explores how teachers implement emotionally responsive teaching strategies across various literary genres, including poems, short stories, and graphic novels. Through in-depth interviews, classroom observations, field notes, and member validation, the research investigates how six experienced teachers foster emotional engagement and meaningful student connections in the language classroom. The findings reveal that teachers employed diverse, genre-specific strategies that encouraged student reflection, empathy, and expressive participation. From promoting independent learning and cultural immersion to integrating visual and hands-on activities, these approaches contributed to emotionally rich classroom environments where students felt valued and understood. The study highlights how emotionally attuned teaching practices can enhance students’ personal development, classroom engagement, and connection to literature. It concludes by emphasizing the role of teacher responsiveness and reflective practice in fostering supportive and inclusive learning environments that nurture both academic and emotional growth.